Hydrothermal synthesis of the novel rutile-mixed anatase TiO2 nanosheets with dominant {001} facets for high photocatalytic activity. Issue 87 (5th September 2016) - Song, Gongsheng; Luo, Chengzhi; Fu, Qiang; Pan, Chunxu
Abstract : We introduce a hydrothermal route to synthesize rutile-mixed anatase nanosheets with dominant {001} facets for high photocatalytic activity. Abstract : In this paper, we introduce a process to synthesize a novel photocatalyst called rutile-mixed anatase nanosheets with dominant {001} facets from a hydrothermal route by using a solution mixed with Ti(OC4 H9 )4, HF, NH4 F and H2 O. The crystal structure, micrographs, chemical compositions, and photocatalytic property are characterized and evaluated by using an X-ray diffractometer (XRD), high-resolution transmission electron microscope (HRTEM), X-ray photoelectron spectroscopy (XPS), UV-vis spectrophotometer, and fluorescence spectrophotometer. The experimental results reveal that (1) the addition of NH4 F played a crucial role, because it not only changes the chemical environment but also make the phase transformation from anatase to rutile. (2) Compared with the regular anatase TiO2 nanosheets with dominant {001} facets, the present novel photocatalyst exhibits a greatly enhanced photocatalyst activity, i.e., its highest level of photocatalytic activity was about four times higher than that of commercial P25 and the regular anatase TiO2 nanosheets with dominant {001} facets. The mechanism is because the formation of the rutile/anatase heterostructure enhances the separation of the photo-generated electrons and holes. It is expected that this novel photocatalyst will provide wide applications in areas of solar cells, hydrogen generation, photocatalytic environmental pollution treatment, etc.